1999
DOI: 10.1128/aem.65.12.5443-5450.1999
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Phylogenetic Analyses of a Cold-Active β-Galactosidase from the Lactic Acid Bacterium Carnobacterium piscicola BA

Abstract: We are investigating glycosyl hydrolases from new psychrophilic isolates to examine the adaptations of enzymes to low temperatures. A β-galactosidase from isolate BA, which we have classified as a strain of the lactic acid bacterium Carnobacterium piscicola, was capable of hydrolyzing the chromogen 5-bromo-4-chloro-3-indolyl β-d-galactopyranoside (X-Gal) at 4°C and possessed higher activity in crude cell lysates at 25 than at 37°C. Sequence analysis of a cloned DNA fragment encoding this activity revealed a ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(12 citation statements)
references
References 36 publications
(35 reference statements)
0
11
1
Order By: Relevance
“…β-Galactosidases, e.g. from Bifidobacterium bifidum, B. infantis [5], Carnobacterium piscicola [6], L. acidophilus [7], L. bulgaricus [8], L. reuteri [9], and Leuconostoc lactis [10], have been cloned and characterised in varying detail. Despite of the importance Research Article β β-Galactosidase from Lactobacillus pentosus: Purification, characterization and formation of galacto-oligosaccharides of LAB and in particular Lactobacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…β-Galactosidases, e.g. from Bifidobacterium bifidum, B. infantis [5], Carnobacterium piscicola [6], L. acidophilus [7], L. bulgaricus [8], L. reuteri [9], and Leuconostoc lactis [10], have been cloned and characterised in varying detail. Despite of the importance Research Article β β-Galactosidase from Lactobacillus pentosus: Purification, characterization and formation of galacto-oligosaccharides of LAB and in particular Lactobacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…coli , it is possible to use other bacterial cell type containing innate β ‐galactosidase gene or introduced by recombinant technology. Nevertheless, various other researchers have already shown that innate cytoplasmic β ‐galactosidase enzyme exists in other microbes such as Enterococcus faecium , Staphylococcus species , Haemophilus sp , Streptococcus pneumonia , Caldariella acidophila , Kluyveromyces fragilis , Kluyveromyces lactis , Aspergillus niger , Aspergillus oryzae , Lactobacillus thermophilus , Leuconostoc citrovorum , Bacillus circulans , Carnobacterium piscicola , Sulfolobus solfataricus , etc . Given this, it is tempting to speculate that this assay method can be extended to other microbes with minor modifications in the incubation time or concentration parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The b-galactosidase bgaC showed its optimum activity at 408C with a half-life of 15 min at 458C. Activity of aand b-galactosidase declined in the C. piscicola in the presence of glucose or lactose media (Coombs & Brenchley, 1999 suitable for treating milk (pH 6.8) and sweet whey (pH 6.2). Lack of stability below pH 6.0 precludes its use for treating acid whey at pH 4.6.…”
Section: B-ga L Ac Tos I Da S E F Ro M L a Cti C Ac I D Ba Cte Ri Amentioning
confidence: 99%